Do unions promote members' electoral office holding? Evidence from correlates of state legislatures' occupational shares - Aaron J. Sojourner (Institute for the Study of Labor (IZA), 2012)
Controversies over the promise and perils of union political influence have erupted around the U.S. This study develops the first evidence on the degree to which labor unions develop members' political leadership in the broader community by studying the relationship between state legislators' occupations and the unionization rates of occupations across U.S. states. The fraction of legislators of a given occupation in a state increases with the occupation's rate of unionization in that state compared to the fraction of legislators of the same occupation in other states with lower unionization rates. This pattern shows up to varying degrees among the three public-sector and one private-sector occupations considered: K-12 teachers, police officers, fire fighters, and construction workers. It holds conditional on differences in observable state characteristics and when using state fixed effects. While much research has described the role of unions in influencing economic outcomes and in politics through lobbying, campaign contributions, and voter mobilization, this work adds a new perspective on the role of unions in society. They promote elected political leadership by individuals from working- and middle-class jobs. Arguments over the social value of this role of unions are explored.
urn:nbn:de:101:1-2012080812160
Keywords: D7; H7; J5; 330; union; elected office; teachers; police; construction; public-sector; Politiker; Erwerbsverlauf; Gewerkschaftsmitgliedschaft; Gewerkschaftspolitik; Interessenpolitik; Teilstaat; USA